Female Offenders' Perceptions of Police Procedural Justice and Their Obligation to Obey the Law. (June 2018) - Baker, Thomas; Gau, Jacinta M.
Although the process-based model of criminal justice has received substantial empirical attention, few previous studies have examined individuals embedded in a criminal lifestyle and at the most risk for future offending, and few have focused exclusively on female offenders. Employing structural equation modeling, the present study tests the process-based model of self-regulation among a sample of 694 incarcerated females. Specifically examined is the effect of perceptions of voice in respondents' most recent encounter with police on their perceptions of police procedural justice and the impact of respondents' procedural justice perceptions on their perceived obligation to obey the law. Results reveal support for the process-based model among serious female offenders, though the impact may be attenuated by increased experience with the criminal justice system. Policy implications are discussed.